Peran Modal Sosial Dalam Program Penanggulangan Kemiskinan Di Kelurahan Betet Kecamatan Pesantren Kota Kediri - Taufiq Al-Amin (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2016)
So far an approach in overcoming poverty, both at the national, regional and local, generally is with a purely economic approach. The problem of poverty seems to be simply understood as a problem of lack of income, so that the prevention programs which are carried out especially by the government focus only on the provision of assistance in the field of capital, the provision of subsidies, aid equipment and the like. This paper uses the form of social capital theory to understand, map out and promote poverty reduction by optimally utilizing social capital in the community. By utilizing social capital theory of Bourdieu, Coleman and Putnam, this research takes place in the Betet Village, Pesantren, Kediri City as the unit of analysis. The basic consideration of the location chosen is that Betet village is one of village areas in Kediri which implements poverty reduction programs since 2009 until now. The result shows that the poverty reduction in Betet village is implemented through a series of stages called PNPM Mandiri Urban cycle; it is started with a reflection of poverty, self power-mapping, determination of a medium-term program of poverty reduction programs. The characteristics of social capital of Betet Village community has grown and developed far before the PNPM program is implemented. The characteristics of social capital includes trust, links that has formed, values and norms that are awakened, participation and pro-active action. The existence of social capital contributes positively to their poverty reduction programs that emphasize community participation in various activities.